1995
DOI: 10.1152/ajpheart.1995.269.1.h320
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced postischemic myocardial recovery following exercise induction of HSP 72

Abstract: The inducible isoform of the 70-kDa heat shock protein (HSP) family, HSP 72, has been shown to protect cells from protein-damaging stressors and has been associated with myocardial protection. Because exercise is capable of increasing HSP 72 content, we determined whether exercise induction of HSP 72 also provided myocardial protection. Twenty-eight rats (n = 7 per group) were divided into control, heat-shocked (15 min at 42 degrees C), and two exercised groups. Exercise consisted of either one or three bouts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
120
1
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(132 citation statements)
references
References 0 publications
10
120
1
1
Order By: Relevance
“…In the youngest group, there was an exercise-induced increase in HSP70 (105%) and catalase (26%) accompanying the improved cardioprotection. It could be concluded that HSP70 is the primary mediator of protection in this age group because the magnitude of the increase was similar to that reported by other studies supporting this chaperone as the primary mechanism of exercise-induced cardioprotection (23,27), and there is considerable data indicating that an elevation of HSP70 is cardioprotective against I/R (for reviews, see Refs. 18, 30, and 31).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In the youngest group, there was an exercise-induced increase in HSP70 (105%) and catalase (26%) accompanying the improved cardioprotection. It could be concluded that HSP70 is the primary mediator of protection in this age group because the magnitude of the increase was similar to that reported by other studies supporting this chaperone as the primary mechanism of exercise-induced cardioprotection (23,27), and there is considerable data indicating that an elevation of HSP70 is cardioprotective against I/R (for reviews, see Refs. 18, 30, and 31).…”
Section: Discussionsupporting
confidence: 85%
“…ENHANCED CARDIOPROTECTION against ischemia-reperfusion (I/R) injury has been observed after one to three exercise bouts (4,11,13,15,23,27,34,36,38). Exercise, along with brief heat shock or ischemia, is among a group of the manipulations that have been reported to induce the late phase of preconditioning against I/R (for reviews, see Refs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, experimental studies have documented that both short-and long-term endurance exercise provides myocardial protection against ischemia-reperfusion injury in rats (6,14,23,30,53,54,77). Several factors, including an increase in calcium handling (14), endogenous antioxidants (50,77), heat shock proteins (50,81), and increased expression of myosin heavy chain-␤ (34) as well as intrinsic metabolic factors and reduced content of the arrhythmogenic substance cyclic AMP, have been implicated as mechanisms responsible for the protective effects of exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, LV levels of HSP72 and HSP73 were assessed by performing polyacrylamide gel electrophoresis and western blotting techniques. 19 In brief, LV samples were homogenized in a buffer containing 10 mM Tris, 10 mM NaCl, 0.1 mM EDTA, 15 mM mercaptoethanol at pH 7.6. Samples (30 mg) were loaded into wells of a 4% polyacrylamide stacking gela12% separating gel (Bio-Rad Mini Protean II Gel apparatus).…”
Section: Hsp Analysismentioning
confidence: 99%